Dark night of the soul - John of the Cross, Saint, 1542-1591.; Silverio de Santa Teresa, 1878-1954; Peers, E. Allison (Edgar Allison), 1891-1952 (Mineola, N.Y. : Dover Publications, 2003)
De Heilige mysticus Johannes van het Kruis beschrijft in dit werk zijn liefde voor God.
Originally published: 3rd ed. Westminster, Md. : Newman Press, 1953. With new introd.
Keywords: Mysticism -- Catholic Church